2022
DOI: 10.3389/fonc.2022.859974
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Amenorrhea and Its Prognostic Significance in Premenopausal Women With Breast Cancer: An Updated Meta-Analysis

Abstract: ObjectiveChemotherapy-induced amenorrhea (CIA) is one of the most common side effects in premenopausal patients with breast cancer, and several factors may contribute to the incidence of CIA. In this meta-analysis, we aimed to summarize clinical risk factors associated with CIA incidence and to evaluate their prognostic effects in patients with breast cancer.MethodsThree electronic databases (Cochrane Library, EMBASE, and MEDLINE) were systematically searched for articles published up to October 2021. The arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 93 publications
0
8
0
2
Order By: Relevance
“…Como dito anteriormente, a amenorreia induzida por quimioterapia, é um sintoma comum nas pacientes prémenopausa e pode estar associada a disfunções geniturinárias, infertilidade e sintomas da perimenopausa, como ondas de calor e suores, sendo um importante tópico, visto que esse aspecto foi um dos mais importantes de acordo com os resultados do presente estudo. Além disso, a preocupação com o potencial futuro de engravidar, tanto relacionado a falência ovariana, quanto a recorrência da doença, é um importante fator psicológico que afeta diretamente a vida das pacientes (Wang;, essa importância está no fato de que a pontuação no questionamento sobre "perspectivas futuras" foi a menor atingida pelas pacientes entrevistadas, na escala funcional, o que significa que há um prejuízo importante.…”
Section: Discussionunclassified
“…Como dito anteriormente, a amenorreia induzida por quimioterapia, é um sintoma comum nas pacientes prémenopausa e pode estar associada a disfunções geniturinárias, infertilidade e sintomas da perimenopausa, como ondas de calor e suores, sendo um importante tópico, visto que esse aspecto foi um dos mais importantes de acordo com os resultados do presente estudo. Além disso, a preocupação com o potencial futuro de engravidar, tanto relacionado a falência ovariana, quanto a recorrência da doença, é um importante fator psicológico que afeta diretamente a vida das pacientes (Wang;, essa importância está no fato de que a pontuação no questionamento sobre "perspectivas futuras" foi a menor atingida pelas pacientes entrevistadas, na escala funcional, o que significa que há um prejuízo importante.…”
Section: Discussionunclassified
“…Another meta-analysis described that when anthracycline-based chemotherapy combined with taxanes was not related to a higher risk of CIA, but the level of evidence was weak (45). In the latest meta-analysis, Wang et al reported that the addition of taxanes to anthracycline-based regimens would significantly increase the CIA rates with no heterogeneity and publication bias (46).…”
Section: The Effects Of Taxanes On Female Menstrual Cyclementioning
confidence: 99%
“…However, these differences were not statistically significant in women older than 40 (40). Fourth, many patients were treated with tamoxifen for a long time, and the use of tamoxifen appears to be associated with higher rates of CIA (46). Consequently, the reported CIA rates may be overestimated.…”
Section: The Effects Of Taxanes On Female Menstrual Cyclementioning
confidence: 99%
“…Alkylating agents and topoisomerase inhibitors, which form the backbone for most breast cancer regimens cause DNA double strand breaks in ovarian follicles and induce their apoptotic death 3 . Whereas taxanes do not induce DNA damage in primordial follicles, and therefore, the addition of a taxane to an AC‐based regimen is not expected to compromise ovarian egg reserve, 4,5 and there have been claims to the contrary based on shorter‐term amenorrhea rates 6 . The topoisomerase inhibitors can also induce microvascular and stromal damage in the ovary 7,8 .…”
Section: Introductionmentioning
confidence: 99%